Pseudoxanthoma elasticum and reflectance confocal microscopy: report of two affected young sisters - Victor Desmond Mandel; Federica Boraldi; Giovanni Pellacani; Silvana Ciardo; Giovanna Mazzaglia; Francesca Farnetani (Hygeia Press di Corridori Marinella, 2015)
Pseudoxanthoma elasticum (PXE) is a rare inherited multisystem disorder that mainly affects skin, eyes and cardiovascular system. The associated clinical signs are due to progressive calcification of elastic fibres and blood vessels, despite normal levels of calcium and phosphorus in blood and urine. The first clinical description of the disease was done in 1881 by Rigal, and in 1896 it was named PXE by Darier. Transmission of the disease is autosomal recessive. PXE is caused by homozygous or compound heterozygous mutations in the ATP-binding cassette subfamily C member 6 (ABCC6) gene, which encodes a transmembrane transport ADP-dependent protein (MRP6). The gene is expressed predominantly in the liver and kidney, and found in low level in the tissue involved by PXE. The clinical expression of PXE is heterogeneous with considerable variation in age of onset, progression and severity of the disease, even in individuals of the same family with identical mutations. We present the case of two young sisters affected by PXE and the correlation between the histopathology and the reflectance confocal microscopy (RCM). Parents and brother carry one copy of the mutated gene, without showing signs and symptoms of the disorder. We report the main clinical aspects of PXE and we highlight the importance of early diagnosis of the disease for adequate therapeutical management of associated complications.